Sex Education (or the Lack Thereof) in Kazakhstan: Heteronormative Propaganda in the Curriculum of Özin Özi Tanu/Samopoznanie - Aizada Arystanbek (Gender a Výzkum)
This qualitative study uses interpretive political and discourse analyses methods to examine how the lack of a sex education policy in the educational curriculum in Kazakhstan and the presence of alternative subjects that focus on the 'moral' education of students is connected to the country's nation-building efforts. Using a feminist critique of gendered nationalism and heteronormativity, the text argues that the lack of comprehensive sex education in the country is consistent with the positioning of women as passive subjects whose bodies are weaponised to delineate cultural and national differences of the group. Kazakhstan's authoritarian government uses the subjects özin özi tanu or samopoznanie (knowing oneself) taught in schools to normalise standards of hegemonic femininity and masculinity among youth. The study examines the official school curriculum and state-issued textbooks and demonstrates how state policy in Kazakhstan seeks to preserve traditional ideas about gender roles and roots them in the national identity. Considering the authoritarian nature of the regime, existing grassroots organisations/efforts that are currently seeking to offer a comprehensive sex education that is not based on traditional gender roles will face a lack of resources and social backlash and will unable to compete with the state's gender ideology.